Health Care Professionals' Perceptions of Pay-for-Performance in Practice: A Qualitative Metasynthesis. (May 2020) - Martin, Barbara; Jones, Jacqueline; Miller, Matthew; Johnson-Koenke, Rachel
Incentive-based pay-for-performance (P4P) models have been introduced during the last 2 decades as a mechanism to improve the delivery of evidence-based care that ensures clinical quality and improves health outcomes. There is mixed evidence that P4P has a positive effect on health outcomes and researchers cite lack of engagement from health care professionals as a limiting factor. This qualitative metasynthesis of existing qualitative research was conducted to integrate health care professionals' perceptions of P4P in clinical practice. Four themes emerged during the research process: positive perceptions of the value of performance measurement and associated financial incentives; negative perceptions of the performance measurement and associated financial incentives; perceptions of how P4P programs influence the quality/appropriateness of care; and perceptions of the influence of P4P program on professional roles and workplace dynamics. Identifying factors that influence health care professionals' perceptions about this type of value-based payment model will guide future research.